Model Ketahanan Ekonomi Rumah Tangga dalam Menghadapi Kenaikan Harga Pangan dan Tekanan Inflasi Global - Hari Suriadi; Martin (Jurnal Ilmu Sosial, Ekonomi dan Pendidikan, 2026)
Rising food prices and persistent global inflation have intensified household economic vulnerability, particularly among low-income families that allocate a substantial share of their expenditures to food consumption. This condition indicates that strengthening household economic resilience requires a comprehensive approach that extends beyond income enhancement alone. This study aims to develop a conceptual model of household economic resilience in responding to rising food prices and global inflationary pressures. The study employs a qualitative approach using a conceptual paper design based on an extensive literature review. Data were collected from peer-reviewed journal articles, academic books, and reports published by national and international institutions and analyzed through content analysis and conceptual synthesis. The findings reveal that household economic resilience is a multidimensional construct shaped by the interaction of five key dimensions: financial resilience, income diversification, household food security, financial literacy, and social protection. Furthermore, global food price volatility, domestic inflation, and increases in strategic food commodity prices were identified as major external drivers that intensify household vulnerability, highlighting the importance of adaptive capacity. The principal contribution of this study is the development of an integrated conceptual model that combines economic, social, and institutional dimensions into a comprehensive analytical framework. The proposed model provides a theoretical foundation for future empirical research and offers policy insights for strengthening household resilience in addressing economic shocks arising from global inflation and food price instability.